Plasma lipid profile of mice fed diet supplemented with broiler fat - Das, GB; Hossain, ME; Akbar, MA (Bangladesh Journal of Animal Science, 2014)
This study was conducted with 180 female Swiss albino mice to examine the effects of supplementing broiler fat in the diets of mice on blood lipid profile. Twenty one days old mice were collected from ICDDRB, Mohakhali, Dhaka. They were randomly distributed in four groups having three replications each. Each replicate group had 15 mice. Results revealed that supplementation of broiler fat in mice diet significantly changed (p<0.05) triglyceride (TG) and low density lipoprotein (LDL) among groups. The control group (T0) had the highest level of cholesterol and LDL. Cholesterol, TG and LDL markedly increased (p<0.05) in all dietary treatment groups, while high density lipoprotein (HDL) significantly (p<0.01) decreased after supplementation of experimental diets. It was concluded that all the dietary treatments in general increased blood cholesterol, TG and LDL in mice fed broiler fat with different oil supplements. However, the soybean and palm oil group was comparatively better than other groups in respect of cholesterol, HDL and LDL at the blood lipid profile of mice. Therefore, it can be concluded that consumption of broiler fat with soybean and palm oil could be less harmful for mice. DOI: http://dx.doi.org/10.3329/bjas.v43i1.19380 Bang. J. Anim. Sci. 2014. 43 (1): 21-24